Boshlangʻich sinf oʻquvchilari nutqini oʻstirishda ertaklarning ahamiyati (SCIENCE and SOCIETY, 2025)
The article presents methods of using fairy tales in the education of children’s speech in primary schools and practical recommendations for primary school teachers.